LPM580098, a Novel Triple Reuptake Inhibitor of Serotonin, Noradrenaline, and Dopamine, Attenuates Neuropathic Pain - Li, Nannan; Li, Chunmei; Han, Rui; Wang, Yu; Yang, Mina; Wang, Hongbo; Tian, Jingwei (Frontiers in Pharmacology, 2019)
Background and purpose: Sedation and somnolence remain serious adverse effects of the existing analgesics (e.g., pregabalin, duloxetine) for neuropathic pain. The available evidence indicates that serotonin (5-HT), noradrenaline (NE), and dopamine (DA) play important roles in modulating the descending inhibitory pain pathway and sleep-wake cycle. The aim of this work was to test the hypothesis that LPM580098, a novel triple reuptake inhibitor (TRI) of 5-HT, NE and DA, has analgesic effect, and does not induce significant adverse effects associated with central inhibition, such as sedation and somnolence. Methods: The analgesic activity of LPM580098 was assessed on formalin test and spinal nerve ligation (SNL)-induced neuropathic pain model. Locomotor activity, pentobarbital sodium-induced sleeping and rota-rod tests were also conducted. In vitro binding and uptake assays, and western blotting were performed to examine the potential mechanisms. Results: LPM580098 suppressed the nocifensive behaviors during phase II of the formalin test in mice. In SNL rats, LPM580098 (16 mg kg-1) inhibited mechanical allodynia, thermal hyperalgesia and hyperexcitation of wide-dynamic range (WDR) neurons, in which the effect of LPM580098 was similar to pregabalin (30 mg kg-1). However, pregabalin altered the spontaneous locomotion, affected pentobarbital sodium-induced sleep, and showed a trend to perform motor dysfunction, which were not induced by LPM580098. Mechanistically, LPM580098 inhibited the uptake of 5-HT, NE, and DA, improved pain-induced changes of the synaptic functional plasticity and structural plasticity possibly via downregulating the NR2B/CaMKIIα/GluR1 and Rac1/RhoA signaling pathways. Conclusions: Our results suggest that LPM580098, a novel TRI, is effective in attenuating neuropathic pain without producing unwanted sedation and somnolence associated with central nervous system (CNS) depressants.